Aktivitas Antioksidan dan Antibakteri Ekstrak Etanol Kulit Batang Lunasia amara - Saputra, Agus; Laut, Meity Marviana; Ndaong, Nemay Anggadewi (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Nowadays, there is an increasing demand for medicines to treat many types of diseases. Lunasia amara is one of the medicinal plants used by Indonesian people for a long time. This study aimed to identify the secondary metabolites of L. amara stem bark using phytochemical analysis and then assess its antioxidant and antibacterial activities. Metabolite extraction will be carried out with an ethanol solvent, and antioxidant activity will be determined using the α, α-diphenyl-β-picrylhydrazyl (DPPH) assays. Antibacterial experiments were conducted against two types of bacteria: Escherichia coli and Staphylococcus aureus. From the results of the phytochemical investigation, the predominant compound group is alkaloid. The ethanol extract metabolites have antioxidant activity and belong to the strong antioxidant group with an IC50 value of 77.96 ppm. Antibacterial activity was weak at concentrations as high as 20%. Based on these findings, further assays can be conducted, such as cytotoxic activity against various cancer cells.